The operas of Sergei Prokofiev - Guillaumier, Christina (Boydell Press, 2020)
The operas of Sergei Prokofiev (1891-1953) mark a significant contribution to twentieth-century music and theatre. Opera was Prokofiev's preferred genre; not counting juvenile and unfinished works, he wrote a total of eight. Yet, to date, little has been published about the context, rationale or musical and compositional processes behind this output. While systematic studies of Prokofiev's symphonies and his ballets exist, the operas have come under no such scrutiny. This book is the first in the English language to engage with the composer's operatic output in its entirety and provides a contextual, critical and musico-analytical account of all of Prokofiev's operas, including those juvenile works that are unpublished as well as the incomplete works composed towards the end of his life. It also includes synopses of the operas. Drawing on a wealth of archival material and other sources, the book provides the compelling untold story of Prokofiev the opera composer.